Factors That are Associated to Physical Fitness (VO2 Max) of Football Athletes - Oktian Firman Bryantara (Jurnal Berkala Epidemiologi, 2016)
Healthy is defined as a state of physical, mental, social, and spiritual well-being. Factors affecting the degree of health and physical fitness of an individual include age, sex, genetics, Body Mass Index (BMI) status, and physical activity. This study aims to analyze factors related to physical fitness (VO2 Max) in soccer athletes. This study was an observational analytic study with a cross-sectional design with a total population of 30 people. This research was carried out at football club X, Nganjuk District from January to June 2015. The variables studied in this study were age, supplement consumption, the status of BMI, and VO2 Max. Data analysis using the Chi-Square test. The results showed that aged 18-35 years (OR = 42; 95% CI = 5.11-345.10), athletes who took supplements (OR = 1.08; 95% CI = 0.24–4.79), normal BMI status (OR = 13.2 95% CI = 2.11 <OR <82.5) has a significant relationship with VO2 Max in soccer athletes. The conclusion of this study is the age of 18-35 years and those who have a normal BMI status have a fitter risk compared to those aged more than 35-45 years and have a fat BMI status. The effort that needs to be done for football club X is to recruit players preferably aged between 18-35 years and have a normal BMI status.